COMPARISON OF LOCAL GOVERNMENT FINANCIAL PERFORMANCE BETWEEN JAMBI CITY AND SUNGAI PENUH CITY FOR THE PERIOD 2020–2024 - Adetiya Purnamasari; Zulfanetti; Dwi Hastuti (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This study is original in that it conducts a comparative analysis of local government financial performance using various financial ratios and statistical tests on two local governments with similar characteristics, namely the City of Jambi and the City of Sungai Penuh, for the period 2020–2024. The objective of this study is to analyze and compare the financial performance of these two local governments. The method used is quantitative descriptive analysis employing financial ratio techniques, including the financial independence ratio, the effectiveness ratio of Local Original Revenue (PAD), the local government financial efficiency ratio, the operational expenditure balance ratio, the capital expenditure balance ratio, and the local government financial growth ratio. Additionally, an independent samples t-test was used to determine differences between the regions. The data used were secondary data in the form of reports on the implementation of the Regional Revenue and Expenditure Budget (APBD). The results of the study indicate that the financial performance of Jambi City is generally better than that of Sungai Penuh City, particularly in terms of financial independence. The results of the t-test indicate significant differences in the financial independence and expenditure balance ratios, while the effectiveness, efficiency, and growth ratios do not show significant differences. The implications of this study emphasize the importance of enhancing local financial independence and optimizing expenditure allocation to improve local government financial performance.